The Effect of Product Quality and Price on the Purchasing Decision of Scarlett in the People of the City of Medan - Maisarah Maisarah; Ainun Mardhiyah (International Journal of Social Science and Community Service, 2025)
The currently beauty products have become one of the primary needs, apart from being used to enhance appearance to make them look more beautiful and attractive, the use of beauty products has also become a lifestyle which is now increasing considered to increase self-cinfidence when using them. In fact,sometimes they don’t hesitate to spend more to get a quality product. There are numerous factors that impact the decisions customers make when it comes to purchasing products and choosing a particular brand, including product quality and pricing. Scarlett must take both of these factors into account in order to effectively compete with other companies. The objective of this study is to examine the impact of product quality and pricing on Scarlett's purchasing choices among consumers in the city of Medan. The connection between the price of a product and its quality will be analyzed in part and at the same time to gain insight into its impact on consumer buying choices. The research employed a quantitative methodology combined with an associative technique. Participants were chosen through purposive sampling, with a sample size of 100 individuals. Throughout the research, the main information was gathered through interviews, questionnaires, and Google Forms, while secondary data was collected from research papers. The analysis included validity and reliability tests, as well as classic assumption, regression, and hypothesis tests. The findings indicate that product quality and pricing are important factors influencing the purchasing decisions of individuals in Medan city. The test of coefficient determination indicates a relatively strong connection between product quality and price in influencing purchasing choices, with an R value of 0.782. The adjusted R square value reveals that product quality and price play a significant role in determining 69.9% of the purchasing decisions, leaving 30.1% to be influenced by other factors not explored in this research.